Dexmedetomidine Attenuates Monocyte-Endothelial Adherence via Inhibiting Connexin43 on Vascular Endothelial Cells - Yunfei Chai; Runying Yu; Yong Liu; Sheng Wang; Dongdong Yuan; Jimei Chen (Mediators of Inflammation)
Current studies have identified the multifaceted protective functions of dexmedetomidine on multiple organs. For the first time, we clarify effects of dexmedetomidine on monocyte-endothelial adherence and whether its underlying mechanism is relative to connexin43 (Cx43), a key factor regulating monocyte-endothelial adherence. U937 monocytes and human umbilical vein endothelial cells (HUVECs) were used to explore monocyte-endothelial adherence. Two special siRNAs were designed to knock down Cx43 expression on HUVECs. U937-HUVEC adhesion, adhesion-related molecules, and the activation of the MAPK (p-ERK1/2, p-p38, and p-JNK1/2) signaling pathway were detected. Dexmedetomidine, at its clinically relevant concentrations (0.1 nM and 1 nM), was given as pretreatments to HUVECs. Its effects on Cx43 and U937-HUVEC adhesion were also investigated. The results show that inhibiting Cx43 on HUVECs could attenuate the contents of MCP-1, soluble ICAM-1 (sICAM-1), soluble VCAM-1 (sVCAM-1), and the nonprocessed variants of the adhesion molecules ICAM-1 and VCAM-1 and ultimately result in U937-HUVEC adhesion decrease. Meanwhile, the activation of MAPKs was also inhibited. U0126 (inhibiting p-ERK1/2) and SB202190 (inhibiting p38) decreased the contents of MCP-1, sICAM-1, and sVCAM-1, but SP600125 (inhibiting p-JNK1/2) had none of these effects. ICAM-1 and VCAM-1 could be regulated in a similar way. Dexmedetomidine pretreatment inhibited Cx43 on HUVECs, the activation of MAPKs, and U937-HUVEC adhesion. Therefore, we conclude that dexmedetomidine attenuates U937-HUVEC adhesion via inhibiting Cx43 on HUVECs modulating the activation of MAPK signaling pathways.